2011
DOI: 10.1002/anie.201007309
|View full text |Cite
|
Sign up to set email alerts
|

On the Macrocyclization of the Erythromycin Core: Preorganization is Not Required

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Earlier Pd-catalyzed macrolactonization methods required a stoichiometric amount of an external oxidant. 83 In 2012, the Breit group developed an atom-economical intramolecular macrolactonization of -alkynoic acids without an external oxidant, where 5-23-membered vinylic lactones were synthesized using the catalytic Rh(I)/DPEphos system (Scheme 64). 84 Due to formation of 'head-to-tail' dimerized side product, the yield decreased in the case of medium-sized rings.…”
Section: Using Oxygen Nucleophilesmentioning
confidence: 99%
“…Earlier Pd-catalyzed macrolactonization methods required a stoichiometric amount of an external oxidant. 83 In 2012, the Breit group developed an atom-economical intramolecular macrolactonization of -alkynoic acids without an external oxidant, where 5-23-membered vinylic lactones were synthesized using the catalytic Rh(I)/DPEphos system (Scheme 64). 84 Due to formation of 'head-to-tail' dimerized side product, the yield decreased in the case of medium-sized rings.…”
Section: Using Oxygen Nucleophilesmentioning
confidence: 99%
“…Compound 84 was characterized and appeared as a single product ( 1 H-NMR evidence); however, no further studies were performed to assign the stereochemistry of the newly formed stereocenter. With the aim to achieve high regio- and diastereo-selectivity, the authors hydrolyzed ester 83 to the corresponding carboxylic acid 86, which was then submitted to intramolecular lactonization via C-H allylic activation using White’s catalyst [ 62 , 63 , 64 ]. After a brief optimization, the authors found that the reaction of 86 with White’s catalyst in the presence of DDQ and Cr(III)salenCl gave lactone 87 as a single diastereoisomer in 40% yield with 50% recovery of the starting material.…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, they extended this methodology to the total synthesis of an erythromycin precursor, 6-deoxyerythronolide B (6-dEB). 57 3.1.1. Regioselective C(sp 3 )-H activation.…”
Section: C(sp 3 )-H Activation Reactions Of Carboxylic Acidsmentioning
confidence: 99%